PROYEK PEMBANGUNAN USAHA JURAGAN LAUNDRY - Agung Wijoyo; Mahdiyana; Muhammad Yasir; Muhamad Zein Akbar; Khantaqwa Amri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
tarting a laundry business can be a business opportunity that can be done anywhere. That the laundry business is one of the right answers in choosing a friendly and safe business. Washing becomes a daily activity, the need for washing for everyone cannot be contested. That's why starting a laundry business can be one of the easiest business opportunities to do, either as a side job or as a main job. For that, knowing the reasons for starting a business opportunity, one of which is a laundry business. And there are several factors that must always be considered before you open a new business, first you don't need to pay rent, it takes a lot of people, you can do it yourself, requires little capital, and a lucrative income.